2012
DOI: 10.1111/j.1708-8208.2011.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Fixed Implant‐Retained Rehabilitation of the Edentulous Maxilla: 11‐Year Results of a Prospective Study

Abstract: Within the limitation of this study, restoration of the edentulous maxilla with an implant-supported fixed prosthesis represents an effective tool for rehabilitation over a period of 11 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 44 publications
3
35
1
9
Order By: Relevance
“…As in this study, several authors have found a significantly higher implant loss 19,20,26,[35][36][37] and increased bone loss 27,38-47 in smokers. As in this study, several authors have found a significantly higher implant loss 19,20,26,[35][36][37] and increased bone loss 27,38-47 in smokers.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As in this study, several authors have found a significantly higher implant loss 19,20,26,[35][36][37] and increased bone loss 27,38-47 in smokers. As in this study, several authors have found a significantly higher implant loss 19,20,26,[35][36][37] and increased bone loss 27,38-47 in smokers.…”
Section: Discussionsupporting
confidence: 77%
“…Mertens et al 26 Other studies have found bone loss greater than 3 mm in between 1% and 13% of implants after 10 or more years of follow-up. 6,11,15,18,25,28 According to our results, it seems that certain factors may have an influence on long-term results of implants such as smoking, osteopenia or osteoporosis, check-up frequency, implant surface, length and position, and type of prosthesis.…”
Section: Discussionmentioning
confidence: 92%
“…Chappuis and colleagues reported an 89.5% cummulative survival rate for the TPS implants after 20 years of follow‐up, with 92% of the implants losing less than 1 mm of bone. Similarly, excellent results were obtained with the TiOblast surface (Astra Tech, Mölndal, Sweden) up to 16 years of follow‐up, with survival rates ranging from 96% to 100% and limited bone loss up to 0.88 mm . However, these implant types have been discontinued and were replaced by new surface treatments.…”
Section: Discussionmentioning
confidence: 95%
“…En este sentido, los avances en el diagnóstico integral del paciente, en la planificación de tratamiento, en las téc-nicas quirúrgicas básicas y complejas, así como en las diversas opciones prostodóncicas (coronas, puentes, rehabilitaciones fijas y sobredentaduras) han desarrollado la implantología oral hasta convertirla en una terapéutica odontológica cotidiana (1)(2)(3)(4)(5)(6).…”
Section: Introductionunclassified
“…Posteriormente, el tratamiento implantológico ha sido aplicado a los pacientes con pérdida dental parcial y unitaria, demostrando ser una alternativa con éxito a las prótesis parciales removibles y fijas, tanto en el maxilar como en la mandíbula (4)(5)(6).…”
Section: Introductionunclassified